The Influence Of Spirit, Leadership Style, And Ethic On Performance Employees Bank BRI Medan - Fitra Arlina Nasution (Jurnal Scientia, 2024)
The impact of work enthusiasm, leadership style, and work ethic on the performance of employees at PT Bank Rakyat Indonesia, Medan Branch. This research aims to determine and analyze the influence of work enthusiasm, leadership style, and work ethic on em-ployee performance. The research uses a quantitative approach and is classified as ex-planatory research. The study was conducted at the PT Bank Rakyat Indonesia Medan Branch office. The population includes all permanent employees at this branch, totaling 64 employees. To ensure a representative sample, the research included the entire popu-lation, resulting in 64 respondents. Data analysis was performed using Descriptive Anal-ysis and Regression Analysis. The results indicate that work enthusiasm, on its own, does not significantly affect employee performance. However, both leadership style and work ethic significantly impact employee performance. Collectively, work enthusiasm, leadership style, and work ethic have a significant effect on employee performance.